(untitled) (Research, Society and Development, 2021)
Natural plants extracts have been used for pharmacological purposes for thousands years. The use in popular medicine has been propagated from culture to culture and described in different literature. Therefore, sought to analyze the benefits of using herbal medicines in view of the recurrent signs and symptoms of the pregnancy period. It is an integrative literature review of a descriptive nature with a qualitative approach. To achieve the results, the abstracts of 284 articles available in full were analyzed as well as patents obtained based on that, the descriptors were crossed. Among these, 26 studies were selected for answering the guiding question: "Can the use of herbal medicines help in the control of signs and symptoms arising from pregnancy?". After reading the studies it was identified that 29 species of plants are used as herbal medicines for the treatment of recurrent symptoms during pregnancy especially the ginger, chamomile, mint and garlic. As for technological prospecting six patents were selected which, in their discussion, reported the pharmacological potential of ginger, watermelon, among others in the treatment of common symptoms during pregnancy. In this way, it is observed that despite the progressive growth in the importance of herbal medicines. Dessarte noted that the progressive growth in the importance of herbal medicines. A few studies have been carried out in order to prove the effectiveness of their use in face of the characteristic symptoms of the pregnancy period and that numerous medicinal plants are still applied from the knowledge well-employed.